2005
DOI: 10.1007/s00776-005-0953-1
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of the neurological outcome of surgery for cervical compressive myelopathy

Abstract: We suggest that multivariate analysis is useful for assessing the neurosurgical outcome in patients with cervical compressive myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 18 publications
2
63
0
Order By: Relevance
“…Cervical spondylosis often manifests with spastic tetraparesis with varying degrees of sensory dysfunction [6,10,11,14,26,45]. Crandall et al [10] indicated that somewhat less than 7% of patients with cervical spondylotic myelopathy present with minimal sensation loss, and classified this subtype of the disorder as cervical spondylotic amyotrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical spondylosis often manifests with spastic tetraparesis with varying degrees of sensory dysfunction [6,10,11,14,26,45]. Crandall et al [10] indicated that somewhat less than 7% of patients with cervical spondylotic myelopathy present with minimal sensation loss, and classified this subtype of the disorder as cervical spondylotic amyotrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased cross sectional area of the spinal cord has also been shown to correlate with neurologic deficits and pathologic cord changes in other neurologic or spinal disorders, such as multiple sclerosis (MS) [34][35][36][37][38][39][40][41][42][43]. It may be hypothesized that the decreased spinal canal and/or spinal cord measurements present in the 22q11.2 population could potentially be predictive of future neurologic risk, particularly as these children grow into adults.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Also in severe compressive myelopathy, spinal cord dimension was correlated with the outcome. [25][26][27] In KFS, however, Samartzis et al advocated that increased space available for the cord would protect from neurologic complication instead of aggravating it. 28 Therefore, it is reasonable to deduce that the spinal cord enlarges as patients with KFS grow.…”
Section: Discussionmentioning
confidence: 99%